Family Centered Empowerment Model Efektif Meningkatkan Mekanisme Koping Orang Tua dalam Merawat Anak Penyakit Kronis - Rahma Fadillah Sopha; Nur Agustini; Imami Nur Rachmawati (Journal of Telenursing (JOTING), 2023)
This study aims to find evidence of the clinical efficacy of the Family Centered Empowerment Model (FCEM) care concept to improve parents' coping mechanisms in caring for children with chronic illnesses. The method used is a systematic review based on guidelines from Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA), which includes e-resources from ProQuest, Science Direct, Scopus, PubMed, and EBSCOhost from 2012 – 2022. Articles included in the systematic review This was made based on the Population Intervention Comparison Outcome Study (PICOS) with a design for (P) Parents/caregivers of children with chronic disease, (I) Concept of Family-Centered Empowerment Model (FCEM) care, (C) There is no comparison intervention, and ( O) Improving coping mechanisms for caring for children with chronic illnesses. The results showed that from 552 articles filtered into eight themes, data found that FCEM can improve parents' coping mechanisms in caring for children with chronic illnesses. In conclusion, FCEM care effectively improves parents' coping mechanisms for children with chronic diseases. Keywords: Family-Centered Empowerment Model, Chronic Disease, Coping Mechanism